A profile design method to improve the wear performance of misaligned water‐lubricated bearing. (7th March 2021) - Wang, Jiefu; Han, Yanfeng; Geng, Zhibo; Xiang, Guo; Wang, Jiaxu; Zhao, Rui
Abstract: The study presents a profile design method to improve the wear performance of misaligned water‐lubricated bearing based on the modified Archard model. This method takes into account the variation of the film thickness under the mixed elastohydrodynamic lubrication (mixed‐EHL). A transient hydrodynamic Reynolds equation model with the Patir–Cheng flow factors is used to predict the evolution of the mixed‐EHL performance over time. The Archard model is extended to predict the time‐varying wear based on the fatigue concept. To verify the effectiveness of the proposed profile design method; the simulation results, including the transient contact pressure, wear depth and wear volume, between the considering and not considering the profile design are compared. To gain insight, several illustrative examples are presented to show the amelioration of the profile design. Parametric studies are reported to show the applicability of the profile design and emphasise the profile height selection. Therefore, the profile design is an extraordinary method to reduce the edge wear.